“DIVULGANDO ANDO Y CONOCIMIENTO DANDO” ATENDAMOS A NUESTRA RESPONSABILIDAD COMO CIENTÍFICOS - Gómez-Otamendi, Edel; Luna-Bautista, Carlos F.; Castelán-Vega, Rosalía; Tamariz-Flores , J. Víctor (RD-ICUAP, 2023)